Relasi Alam dan Perempuan dalam Novel Dlumū Lā Tajiffu Karya Byar Rufael: Kajian Ekofeminisme - Saladin, Cundarojat Sidiq; Rohanda, Rohanda (Universitas Lampung, 2024)
Ecofeminism views that exploitation of nature is directly proportional to men's oppression of women. This study aims to present some forms of nature and women relations contained in the novel Dlumū Lā Tajiffu by Byar Rufael. The data of this research is in the form of sentences from the novel Dlumū Lā Tajiffu related to the relation between nature and women. This research belongs to descriptive qualitative research. The approach applied in this research is the relationship between nature and women from the perspective of ecofeminism. The data collection techniques used include the documentation method with reading and recording techniques, and through two data analysis techniques, namely identification and analysis. The results of this study show that the novel Dlumū Lā Tajiffu by Byar Rufael represents the relationship between nature and women in (1) the depiction of the image of nature and women symbolized as a sacred entity, namely the mother. (2) the oppression of nature and women by patriarchal-capitalists such as As'ad Syahdan makes it difficult for villagers to get water. Keywords: Ecofeminism, Women, Ecology, Ecocritism